Descriptive Study of Oral Health in an Indigenous Child Population of Baka Pygmies in Cameroon - Nicias Afoumpam Poni; David Ribas-Pérez; Javier Flores-Fraile; Paloma Villalva Hernández-Franch; Diego Rodríguez-Menacho; Antonio Castaño-Séiquer (MDPI AG, 2023)
Indigenous populations around the world experience a disproportionate burden of oral diseases and health conditions. These inequalities are likely due to a complex web of socioeconomic, cultural, and health determinants. The Baka pygmies of southern Cameroon find themselves in this context of an indigenous population with health inequities. The purpose of this study was to describe the oral health status, diet, hygiene habits, and access to health services of the Baka pygmy children, from which different care needs will emerge in order to develop health strategies. A descriptive cross-sectional study was conducted in 22 Baka pygmy camps randomly selected. The study population consisted of children aged 5-6 years and 11-12 years chosen by a consecutive sampling technique. The examination was performed using a data sheet based on World Health Organization (WHO) criteria and recommendations which consisted of an oral health questionnaire for children and an oral health assessment form for children. A total of 120 children participated in the study. Extraoral examination of the study population revealed the presence of noma (1%) in the age range of 5-6 years. A total of 2713 teeth were examined, and the DMFT/dft index of the sample was 0.71 with a predominant caries component. The periodontal status showed 87% bleeding on probing. Seven percent of the sample presented a need for immediate urgent treatment due to pain and/or infection. Eighty-seven percent of the sample reported never having been examined by a dentist. The examination and oral care they received was only from nongovernmental organizations (NGOs). The conclusion of this descriptive study is that the precarious oral health situation of pygmy children combined with the absence of care services in general for the Baka pygmies generate a situation of great vulnerability.